2016
DOI: 10.4172/2472-1018.1000109
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Fungal Rhinosinusitis: An Observational Study in an Indian Tertiary Care Hospital

Abstract: Invasive fungal rhinosinusitis (IFRS) is a challenging condition and the mortality of IFRS in immuno compromised patients is very high. 75 patients of suspected FRS were included to study the burden and the clinicopathological and mycological profile of invasive fungal rhinosinusitis (FRS) in these patients. The samples collected were exudate from nasal debri, discharge and intraoperative tissue sample and were subjected to direct microscopy to histopathological examination and direct microscopy (KOH and calco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…In a similar study conducted by Das et al in patients with a mean average age of 31 years, male patients were predominantly affected with a male:female of 1.8:1. 10 Higher incidence rates were targeted at people belonging to the third decade (28%) that were also found in the reports of Kaur et al 11 Predominant incidence in FRS in people belonging to the lower socio-economic group, coolie was recorded. This might be due to the increased susceptibility of their exposure to fungal spores.…”
Section: Discussionmentioning
confidence: 57%
“…In a similar study conducted by Das et al in patients with a mean average age of 31 years, male patients were predominantly affected with a male:female of 1.8:1. 10 Higher incidence rates were targeted at people belonging to the third decade (28%) that were also found in the reports of Kaur et al 11 Predominant incidence in FRS in people belonging to the lower socio-economic group, coolie was recorded. This might be due to the increased susceptibility of their exposure to fungal spores.…”
Section: Discussionmentioning
confidence: 57%
“…In non-COVID AIFRS patients, Mucor species were the most common isolates as reported by Kursun et al [31] Bellazreg et al [32] and Kaur et al [33] However, Montone et al [18] reported Aspergillus spp. were the most common causative agents (49%) followed by Rhizopus spp.…”
Section: Discussionmentioning
confidence: 84%